The Effect of Blended Learning Model with Moodle on the Students’ Writing Achievement - Muhammad Arifin (UMSU, 2020)
This study is an experimental research that aims to investigate the effect of the Blended Learning Model with Moodle on the students’ writing achievement. This research was conducted at SMK Tritech Informatika on Jalan Bhayangkara No. 484 Kecamatan Medan Tembung. The samples of the study were the eleventh-grade students of the first semester in the 2019/2020 academic year. There were two parallel classes, which each class consisted of 18 students. The researcher administered a pre-test and post-test about writing news item text to the students to obtain the data. Then, the researcher analyzed the data using a t-test to determine the effect of the model used. The result of the analysis shows that there was a difference in writing achievement between the students who were taught using Blended Learning Model and those who were taught using the conventional method. The value of the t-test proved it. the t-score was 3.12 and t-cv at the level of significance of 0.05 (1.690), which means that t-test (3.12) >t-cv (1.690). Based on the research finding, this study concludes that Blended Learning Model has a significant effect on the students' writing achievement.